THE EFFECTIVENESS OF BRAIN GYM ON CONCENTRATION ON CHILD AGE TODDLER - Hapsari, Dina Carolina; Sulastri, Titi (Fakultas Ilmu Kesehatan, 2023)
Concentration is a person's attention that is only directed at an object, with the nature of being somewhat fixed, firm, strong and not easily shifting one's attention to other objects, while brain gym is exercise or movement Which used For increase Power remember And concentration. The aim of this research is to find out whether there is effectiveness in doing Brian Gym in increasing children's concentration power. Method in study This will use quantitative pre-experiment with design one- groups pretest-posttest design Where study This No There is group comparison but use group Which Already There is For in measuring difference score concentration before And after did it treatment on sample that Already There is. Results study And discussion Which served researcher in chapter This based on Data collection was carried out on 05-08 May 2023 in the RT 002 RW 015 area Tanjung Priok Village, North Jakarta. the number of respondents who were research subjects was 10 person respondents with technique total sampling in where samples Which taken is all over population involved. Based on the research and studies that have been carried out, it can be concluded that brain exercises have a positive influence on children's concentration. Brain exercise involves physical movement and brain exercise that stimulates blood flow and the release of chemicals who plays a role in improving concentration and focus. Keywords: Brain Gym , Concentration Power, Toddler Age Children